Análise dos requisitos para reconhecimento de diplomas estrangeiros no Brasil - Langeloh, Marcia Maria Mattos (2019)
To be considered equivalent to those granted in Brazil and to be lawfully used in the country, strictu sensu graduate degrees (Masters and Doctoral) obtained abroad must be submitted to a validation (or recognition) process. That is done by higher education institutions accredited by the Ministry of Education, that provide degrees of the same or higher level than that of the degree of the process, in the same area of knowledge. This thesis aims to obtain, by consulting specialists, a hierarchy of criteria, stratified by knowledge area, to analyze the requirements for recognition of degrees, with the objective of optimizing the decision-making process. The methodology consisted of two steps, which were applied in a Brazilian higher education institution. In the first step, using focus groups, criteria present in the law are submitted to validation by members of the Assembly of Graduate Studies. In the second step, validated by the focus group were used to construct a survey, which was answered by the directors of each Graduate Program of the institution. Survey answers were organized in matrices of pairwise comparisons of criteria, which were analyzed using elements of the AHP (Analytical Hierarchical Process) method. Criteria were finally ranked according to each area's perceived importance, where an area is an aggregate of similar Graduate Programs.